2015
DOI: 10.1186/s12886-015-0053-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of allergic conjunctivitis among basic school children in the Kumasi Metropolis (Ghana): a community-based cross-sectional study

Abstract: BackgroundThere seems a preponderance of hospital-based studies on the prevalence of Allergic Conjunctivitis (AC) compared to community-based ones, particularly among children in Ghana and Africa as a whole. Meanwhile, literature supports the possibility of underdiagnosing AC in the hospital setting; exponentially so when males generally have poor hospital-attending behavior. This may lead to underestimation of the true burden of AC. Consequently, the purpose of the current community-based study was to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
25
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 29 publications
7
25
2
Order By: Relevance
“…A study in Ghana estimated the prevalence of AC in 5-to 16-year-old school children at close to 40% (Kumah et al 2015). Other studies report an increasing prevalence of allergic conditions among Asian children (Fok & Wong 2009).…”
Section: Introductionmentioning
confidence: 98%
“…A study in Ghana estimated the prevalence of AC in 5-to 16-year-old school children at close to 40% (Kumah et al 2015). Other studies report an increasing prevalence of allergic conditions among Asian children (Fok & Wong 2009).…”
Section: Introductionmentioning
confidence: 98%
“…However, other community based studies among school children indicated a higher prevalence of 17.3 and 39.9 % respectively [11, 12]. Not only is it prevalent among children but several other studies have reported relatively higher prevalence than cataract and glaucoma among adults in Ghana [13, 14] yet it has not received the necessary attention accorded these other ocular disorders [15].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies elsewhere in Hong Kong and France involving pediatric patients report that up to 30 and 32 % of children with allergies respectively had ocular symptoms as the sole manifestation of their allergic disorder [12, 16, 17]. This makes ocular allergy one of the most common ocular diseases encountered in clinical practice, especially among children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not surprising as our study subjects are generally more educated than the general population. Most of the signs and symptoms identified in this study are due to the common ocular conditions (among school children) reported in the country: conjunctivitis and refractive error [25][26][27][28]. Results from the study were indicative of the fact that teachers had the right attitude towards child eye health.…”
Section: Discussionmentioning
confidence: 62%